Rural electrification: Waste biomass Russian northern territories. Final report - Adamian, S. (National Renewable Energy Laboratory (U.S.), 1998)
The primary objective of this pre-feasibility evaluation is to examine the economic and technical feasibility of replacing distillate fuel with local waste biomass in the village of Verkhni-Ozerski, Arkhangelsk Region, Russia. This village is evaluated as a pilot location representing the off-grid villages in the Russian Northern Territories. The U.S. Department of Energy (DOE) has agreed to provide technical assistance to the Ministry of Fuel and Energy (MFE). MFE has identified the Northern Territories as a priority area requiring NREL`s assistance. The program initially affects about 900 off-grid villages. Biomass and wind energy, and to a lesser extent small hydro (depending on resource availability) are expected to play the dominant role in the program, Geothermal energy may also have a role in the Russian Far East. The Arkhangelsk, Kariela, and Krasnoyarsk Regions, all in the Russian Northern Territories, have abundant forest resources and forest products industries, making them strong candidates for implementation of small-scale waste biomass-to-energy projects. The 900 or so villages included in the renewable energy program span nine administrative regions and autonomous republics. The regional authorities in the Northern Territories proposed these villages to MFE for consideration in the renewable energy program according to the following selection criteria: (a) Remote off-grid location, (b) high cost of transporting fuel, old age of existing power generation equipment, and (d) preliminary determination as to availability of alternative energy resources. Inclusion of indigenous minorities in the program was also heavily emphasized. The prefeasibility study demonstrates that the project merits continuation and a full feasibility analysis. The demonstrated rate of return and net positive cash flow, the willingness of Onegales and local/regional authorities to cooperate, and the immense social benefits are all good reasons to continue the project.